2005
DOI: 10.2106/00004623-200507000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function in Adolescent Idiopathic Scoliosis Relative to the Surgical Procedure

Abstract: Kim, Yongjung J.; Lenke, Lawrence G.; Bridwell, Keith H.; Kim, Kyoungnam L.; and Steger-May, Karen, ,"Pulmonary function in adolescent idiopathic scoliosis relative to the surgical procedure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
0
23
2
2
Order By: Relevance
“…However, APVCR had fallen out of favor for several factors. Anterior transthoracic procedures were challenging for most orthopedists and proved to have detrimental effects on pulmonary function [33][34][35][36][37]. And it was difficult to approach the concavity of the angular kyphosis in deformities greater than 60° [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, APVCR had fallen out of favor for several factors. Anterior transthoracic procedures were challenging for most orthopedists and proved to have detrimental effects on pulmonary function [33][34][35][36][37]. And it was difficult to approach the concavity of the angular kyphosis in deformities greater than 60° [25].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PVCR often needs bilateral costotransversectomies and removal of medial ribs. And it had been reported that any disruption of chest cage might have a negative effect on pulmonary function [33,35,36,38]. So preservation of pulmonary function with PVCR was suspectable.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [27] found that there were deleterious effects on pulmonary function when open anterior approach was added to posterior spinal fusion. Posterior approach can receive similar outcomes comparing to anterior and posterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…19 No patient was lost during a minimum two-year follow-up. In our experience, posterior VCR is most suitable for patients with a pure kyphosis or kyphoscoliosis, as in these patients the exposure of the vertebral column is easier than with hypokyphotic or lordotic scoliosis.…”
Section: Discussionmentioning
confidence: 97%